Synchronization of dehydration and phosphorous immobilization for river sediment by calcified polyferric sulfate pretreatment. (April 2021) - Yang, Nan; Xiao, Hang; Pi, Kewu; Fang, Jing; Liu, Shuze; Chen, Yuhan; Shi, Yafei; Zhang, Huiqin; Gerson, Andrea R.; Liu, Defu
Abstract: Disposal of dredged river sediment requires decreases in both water content for reduction in disposal area, and the amount of eutrophication pollutants at risking of leaching. The effects of CaCl2, polyferric sulfate (PFS) and calcified polyferric sulfate (CaPFS) on dewatering and phosphorus immobilization were examined. Upon CaPFS dosage of 1.88 mg Ca + Fe kg −1 raw sediment (RS) the moisture content of the sediment was 41.1 wt% after pressure filtration, with filtrate dissolved inorganic phosphorus (DIP) of 6.1 mg L −1 ; better outcomes than for equivalent dosages of CaCl2 or PFS. On CaPFS dosage of 4.98 mg Ca + Fe kg −1 RS, DIP in the filtrate was <0.5 mg L −1 . Dosages of CaCl2 and PFS required to achieve <0.5 mg L −1 DIP were 6.79 mg Ca kg −1 RS and 5.64 mg Fe kg −1 RS. CaPFS aids particle surface charge neutralization and sweep flocculation by polymeric iron, improving dehydration efficiency. Synergistic effects of aqueous Ca and Fe promote P stability reducing DIP mobility. For treatment of 10000 m 3 of this dredged sediment, CaPFS has the potential to reduce the discharge of eutrophicated water by 74 ± 6% compared with PAC + PAM conditioning, demonstrating the promising application of CaPFS conditioning. Highlights: Study of dewatering and P immobilization of dredged black-odor water sediment. Calcified polyferric sulfate conditioning yielded the best outcomes. Polymeric Fe flocculation of Ca–P and sediment particles promotes P effective removal. Transformation from unstable NH4 Cl–P and Al/Fe–P to stable Ca–P and Res-P by CaPFS. Cleaner strategy for black-odor water treatment developed.